The sprint start: Biomechanical analysis of kinematic, dynamic and electromyographic parameters - Coh, M.; Peharec, S.; Bacic, P. (New Studies in Athletics, 2007)
The start and transition to the acceleration phase of a sprint race is a very complex movement sequence, requiring high muscle activation and effective integration of acyclic and cyclic movements. The purpose of the study was to understand the mechanisms of the start and facilitate the development of appropriate training methods for one athlete, a female hurdler with a best time of 13.19. The aim was to measure the major kinematic and dynamic parameters as well as the EMG activation of muscles in the start. The focus was on 1) the block velocity in a dependent relationship with the development of force in the rear and front blocks, 2) the block acceleration in the first two steps and 3) the EMG activity of seven key muscles. The results of the study include data on 15 start-related parameters and analysis of the EMG activity in both legs during the start.